Effect of an elongation bending derotation brace on the infantile or juvenile scoliosis - Thometz, John (Scoliosis Spinal Disord, 2018)
BACKGROUND: A wide variety of braces are commercially available designed for the adolescent idiopathic scoliosis (AIS), but very few braces for infantile scoliosis (IS) or juvenile scoliosis (JS). The goals of this study were: 1) to briefly introduce an elongation bending derotation brace (EBDB) in the treatment of IS or JS; 2) to investigate changes of Cobb angles in the AP view of X-ray between in and out of the EBDB at 0, 3, 6, 9, and 12 months; 3) to compare differences of Cobb angles (out of brace) in 3, 6, 9, and12 month with the baseline; 4) to investigate changes (out of brace) in JS and IS groups separately. METHODS: Thirty-eight patients with IS or JS were recruited retrospectively for this study. Spinal manipulation was performed using a stockinet. This was done simultaneously with a surface topography scan. The procedure was done in the operating room for IS, or in a clinical setting for JS. The brace was edited and fabricated using CAD/CAM method. Radiographs were recorded in and out of bracing approximately every 3 months from baseline to 12 months. A linear mixed effects model was used to compare in and out of bracing, and out of brace Cobb angle change over the 12 month period. RESULTS: Overall, 37.5% of curves are corrected and 37.5% stabilized after 12 months (Thoracic curves 48% correction, 19% stabilization; thoracolumbar curves 33% correction, 56% stabilization and lumbar curves 29% correction, 50% stabilization). The juvenile group had 25.7% correction and 42.9% stabilization, while the infantile group had 50% correction and 32.1% stabilization. There was a significant Cobb angle in-brace reduction in the thoracic (11°), thoracolumbar (12°), and lumbar (12°) (p < 0.001). There was no statistically significant change in out of brace Cobb angle from baseline to month 12 (p > 0.05). No patients required surgery within the 12 month span. CONCLUSIONS: This study describes a new clinical protocol in the development of the EBDB. Short-term results show brace is effective in preventing IS or JS curve progression over a 12 month span.